Management of Primary Female Urethral Adenocarcinoma: Two Rare Case Reports and Literature Review - Junjie Tian; Ting Zhu; Zhijie Xu; Xiaoyi Chen; Yunfei Wu; Guanghou Fu; Baiye Jin (Medicina, 2023)
Primary urethral adenocarcinoma in females is an extremely rare malignancy with unclear origin and only a few retrospective cases have been reported. The controversy continues to exist over the origin of primary urethral adenocarcinoma from periurethral glands (which include the Skene’s glands), urethritis glandularis or intestinal metaplasia. Herein, we report one case of a 49-year-old female with distal urethral adenocarcinoma who presented with obstructive voiding. Abdominal and pelvic CT scans and chest radiology were unremarkable. Biopsy of the mass confirmed urethral adenocarcinoma. The patient underwent partial ureterectomy and was disease-free at the 2-years follow-up period. We also present another extremely rare case of primary urethral adenocarcinoma with mucinous features in a 58-year-old female who initially complained of external urethral orifice itching with painless urethral bleeding and was treated with local excision. The patient has not received any neoadjuvant or adjuvant therapy, and experienced tumor recurrence, inguinal lymph nodes metastasis, and even local iliopsoas metastasis during over 10-years follow-up. In conclusion, our current study emphasizes the importance of imaging studies and biopsy in making an accurate preoperative diagnosis of this rare disease, and further highlights the role of multimodal therapy. A combination of radiotherapy, chemotherapy and surgery is recommended for the optimal local and distant disease control. Moreover, better medical compliance and regular follow-up are required in these patients.